Interplay between foreign direct investment, institutional quality and economic growth - Tun, Yin Li (2011)
Foreign direct investment (FDI) is considered as one of the key ingredients in the development process for many countries. It is viewed as one of the important channels for the transfer of new knowledge across borders. Based on these potential positive spillovers, many countries have eased restrictions on the flows of foreign capital. As a result, FDI inflows increased significantly over the past few decades. However, increase in FDI is not uniform across countries as few countries are able to attract more FDI than the others. Another important issue related to FDI is that not all FDI recipients seem to benefit from FDI inflows. Evidence shows that the impact of multinational corporations (MNCs) presence on the growth of host economies is ambiguous. In some cases, FDI exerts positive impacts on growth but in some other cases there is no or even negative impacts. One of the key explanations for this ambiguity that appears in recent literatures is the impact of FDI on growth depends on other intervening factors, broadly called “absorptive capacity”. Although evidence on the impact of FDI on economic growth is ambiguous, there is broad theoretical and empirical support for the positive contribution of institutional development in sustaining and promoting economic growth. This study takes a step further by exploring the role of institution in attracting FDI inflows as well as in mediating the positive growth-effects of FDI. It argues that good institutional quality not only able to attract more FDI inflows but also allow the host countries to benefit from MNCs presence through the absorption and internalization of new knowledge that they bring. To test these hypotheses, it uses a generalized method of moments panel estimator and data from 78 countries. Two important conclusions emerge. First, good institutional quality is found to be important pre-condition for host countries to attract more FDI inflows. Secondly, the impact of FDI on growth actually depends on the quality of institution in the host countries. Countries that promote good institutional quality benefit more from MNCs presence.